Green Solvents for Lipid Extraction From Microalgae to Produce Biodiesel - Liu, Xiaofang; Yu, Dayong; Luo, Hangyu; Li, Can (Frontiers in Chemistry, 2022)
Microalgae are considered as the third-generation feedstock for biodiesel production, and lipid extraction plays a significant role in efficient production of biofuels. Numerous technologies including chemical, mechanical, and biological have been achieved but high efficiency and potential application on an industrial scale are still needed. This review discusses the factors that influence biodiesel quality and the relative green and sustainable solvents for lipid extraction.